The poison squad [videorecording (DVD)] - Maggio, John; Stoll, Corey, 1976-; Blum, Deborah, 1954- (American experience (Television program), 2020)
By the close of the Industrial Revolution, the American food supply was tainted--by frauds, fakes, and legions of new, untested chemicals--all threatening the health of consumers across the country. Based on the critically acclaimed book by Deborah Blum, it tells the story of crusading government chemist Harvey Washington Wiley, the man who led the pure food movement against the food manufacturing industry in the early years of the twentieth century, embarking upon a series of bold and controversial trials on twelve subjects--who would become known as the "Poison Squad." Wiley's experiments and tireless advocacy laid the groundwork for the United States' consumer protection laws, and ultimately the creation of the FDA.